Demographic determinants of the power of the state - Paluch, Alicja (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Connections between demographic conditions of the state and its power have become a reason for the author’s attempt to identify key power-building factors featuring demographic nature. For this purpose, a statistical analysis based on data from selected European countries such as Poland, Czech Republic, Slovakia, Hungary, Germany and Romania was carried out. The outcome of the research allowed the author to obtain six groups of explanatory variables for the model of assessing the power of the state in the demographic area.
Keywords: power of the state; power-building factors; demographic factors